High performance HRM and establishment performance in Pakistan: an empirical analysis. Issue 5 (3rd August 2015) - Ahmad, Mansoor; Allen, Matthew
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Despite a growing literature on human resource management (HRM) in emerging economies, evidence from Pakistan is limited. There is scant information on both the human resource (HR) practices that indigenous workplaces adopt and their associations with HR-related outcomes. The purpose of this paper is to fill that gap by examining whether universalistic assumptions about the applicability of "high-performance" HR practices are valid in Pakistan, a country with religious values and organizational traditions that differ to those in the west. Design/methodology/approach – This study draws on the, to date, most comprehensive survey of indigenous establishments in Pakistan. The authors use logistic regressions to analyze the data. Findings – Workplaces, in general, adopt several "high-performance" HR practices, such as extensive training, career breaks, rigorous pre-employment candidate assessment, and the sharing of strategic information with employees. Attitude surveys and the provision of training in a variety of jobs to non-managerial employees are consistently associated with better HR-related outcomes (absenteeism, quit rates, and labour productivity). Overall, the paper finds some limited support for the applicability and efficacy of high-performance HRM practices in Pakistan. Such practices conform to Islamic principles. The results also indicate, however, that cultural traits play a role in how those practices are implemented. Social implications – Increased adoption of certain HR practices by establishments in Pakistan may help to improve the working conditions and employment prospects of employees and may also ameliorate the country's sluggish economic growth rates. Originality/value – HRM in Pakistani establishments has received relatively scant attention. Existing research either focuses on a relatively small number of firms, assesses HR in MNC subsidiaries, or examines a limited range of HR practices. Understanding the HR practices that are (and are not) adopted and their associations with performance outcomes will not just enhance the knowledge of HR in emerging economies, but will also provide insights into how to improve establishment performance and economic growth rates.